Direct Conversion of Syngas to Higher Alcohols over a CuCoAl|t‐ZrO2 Multifunctional Catalyst. Issue 13 (10th May 2021) - Huang, Chao; Zhu, Can; Zhang, Mingwei; Lu, Yongwu; Wang, Qianhao; Qian, Heming; Chen, Jiangang; Fang, Kegong
Abstract: Selective synthesis of higher alcohols from syngas is promising but remains challenging owing to the low stability and selectivity towards higher alcohols. Here we introduce a CuCoAl|t‐ZrO2 (t denotes tetragonal crystal phase) multifunctional catalyst that can achieve an alcohol selectivity of 64.8 % with 79.6 % C2+ OH, and a total selectivity of alcohols and olefins to 81.7 %. The proper proximity was tuned to increase selectivity towards alcohols and decrease the selectivity towards hydrocarbons. The lower surface [H*]/[C*] ratio due to the stronger basic sites of the CuCoAl|t‐ZrO2 limited alkyl (CHx ) species hydrogenation, and promoted CO insertion and carbon chain growth, resulting in improving the alcohols selectivity. Meanwhile, the weaker adsorption of bridge‐type adsorbed CO and the lower decomposition rate of multi‐bonded adsorbed CO over CuCoAl|t‐ZrO2 inhibited hydrocarbon generation. The selective promotion of the reaction route via the synergetic effect between CuCoAl and t‐ZrO2 was proposed to boost higher alcohols selectivity. This work may aid the rational design of effective multifunctional catalyst with synergistic effects for tuning selectivity. Abstract : Synergetic effect : The physically mixed CuCoAl|t‐ZrO2 multifunctional catalyst could achieve superior selectivity towards alcohols while simultaneously inhibiting the generation of hydrocarbons from CO hydrogenation.